Identification of mRNA Coding for Factor VII Protein in Human Alveolar Macrophages - Coagulant Expression May Be Limited Due to Deficient Postribosomal Processing - McGee, Maria P; Wallin, Reidar; Devlin, Robert; Rothberger, Henry (Thrombosis and Haemostasis, 1989)
Clotting factors synthesized by monocytes and macrophages may initiate coagulation reactions during inflammation. Functional vitamin K-dependent coagulation factors have been found to be associated with human monocytes/macrophages, but there are no reports identifying mRNA coding for vitamin K-dependent proteins in these cells. In the present studies, factor VII mRNA was found in total RNA extracted from freshly isolated human alveolar macrophages using hybridization with a complementary DNA probe. On the other hand, vitamin K-dependent carboxylase activity which is required for postribosomal modification of the protein, was not detectable in the macrophages before or after culture, and human blood mononuclear leukocytes also lacked this enzyme activity. Control human and rat hepatoma cells exhibited high levels of carboxylase activity within the same experiments. Using sensitive kinetic assays, no increase in factor VII activity was detected during culture of alveolar macrophages under conditions promoting 1.78 ± .24 (n = 8) fold increases of tissue factor activity. These findings with freshly isolated cells demonstrate that alveolar macrophages synthesize factor VII mRNA in vivo. However, the mRNA was found in the absence of evidence for γ-carboxylase activity or processing of the factor into a functional clotting enzyme. The results imply that functional expression of any synthesized coagulation factor VII in alveolar macrophages may be limited or prevented due to a cellular deficiency at the level of postribosomal processing.
Keywords: Tissue factor; Factor VII; Vitamin K; Alveolar macrophages